Transcriptome analysis and the effects of polyunsaturated fatty acids on the immune responses of the critically endangered angtze sturgeon (Acipenser dabryanus). Issue 94 (November 2019) - Chen, Hu; Wang, Bin; Yu, Nianye; Qi, Jingwen; Tang, Ni; Wang, Shuyao; Tian, Zhengzhi; Wang, Mei; Xu, Shaoqi; Zhou, Bo; Long, Qiaoling; Chen, Defang; et al.
Abstract: The poor understanding of nutrition needed has become a significant obstruction to artificial conservation of Yangtze sturgeon ( Acipenser dabryanus ) and the relationship between ployunsaturated fatty acid nutrition and the immune response of Yangtze sturgeon is remains unclear. To explore this relationship, the immune response was determined by the activities of serum immune-related enzymes and the transcriptome pattern in the spleen after feeding different fat source diets for 7 weeks. In addition, the gene expression pattern after a lipopolysaccharide (LPS) challenge was investigated in the presence of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). Long-term feeding of the fish oil diets increased the serum immune-related enzyme activities, including lysozyme, acid phosphatase, and alkaline phosphatase of Yangtze sturgeon. More than 653, 999 transcripts with an N50 length of 1047 bp were obtained and a final set of 280, 408 unigenes was generated. After annotating the unigenes, 3549 genes were assigned to the immune system and 2839 were identified to participate in the response to the different fat sources. A transcriptome assay showed the fish oil diets moderately upregulated immune-related signaling pathways in the spleen of Yangtze sturgeon, including NLR signaling, platelet activation, Fc gamma R-mediated phagocytosis, Th17 cell differentiation, and Th1 and Th2 cell differentiation. The quantitative polymerase chain reaction (qPCR) results of candidate genes for these pathways showed similar results. The LPS challenge study revealed that DHA and EPA moderately upregulated the candidate immune-related genes and modulated excessive activation of the immune pathway by the pathogen. This study confirmed the immunomodulatory function of unsaturated fatty acids in Yangtze sturgeon. This research will provide a reference for the preparation of artificial diets for Yangtze sturgeon. Highlights: Fish oil diet improves innate immune enzyme activity in the Yangze sturgeon. The expression pattern of the spleen in the fish oil diet group was moderately regulated in a broad-range of immune relevant pathways. The qPCR results of the transcriptome validation candidate gene are consistent with those obtained by the transcriptome. DHA and EPA in fish oil are beneficial to prevent inflammation caused by LPS-induced excessive immune response. Abstract : The authors have nothing to disclose.